Self-efficacy and Adherence to Treatment in Elderly People with Hypertension at The Dau Community Health Center, Malang Regency - Kusumaningrum, R.A Rusiadela; Sipollo, Berliany Venny; Sakti, Ifa Pannya (Jurnal Keperawatan Profesional (KEPO), 2025)
An older adult was defined as someone who experienced the natural aging process, which led to physiological changes including the development of hypertension. It was important for individuals with hypertension to consistently take their medication, as adherence helped to control blood pressure effectively. Self-efficacy, defined as a person's belief in their ability to manage their own health, was a major factor influencing medication adherence. This study aimed to examine the relationship between self-efficacy and medication adherence among older adults with hypertension at Puskesmas Dau, Malang District. The study employed a quantitative correlational design with a cross-sectional approach involving 52 subjects. Data were collected using the Multidimensional Self-Efficacy Scale-Revised (MASES-R) to assess self-efficacy and the Morisky Medication Adherence Scale (MMAS-8) to measure medication adherence. The findings indicated a significant positive relationship between self-efficacy and medication adherence in older adults with hypertension at Puskesmas Dau, with a p-value of 0,000. The strength of this relationship was categorized as strong and positive.